Paper City Tales: Paper Models for Retelling Italo Calvino’s Invisible Cities (diségno, 2024)
The work presented here involved the creation of paper models of Italo Calvino’s Invisible Cities [Calvino 2009], using different paper cutting and folding techniques to invent sets, forms, structures, and backdrops.In the book’s introduction, the author emphasizes how a layering of many elements characterizes cities. This characteristic led to the creation of models through different levels, which go to define a ‘microcosm’, a city in miniature perceptible through the senses, which becomes an object “to be thought, to be touched, to be looked at” [Croset 1987, p. 48].From a technical point of view, the procedures adopted refer to research on paper folding, carried out by Joseph Albers [The Public Paperfolding History Project 2023] at the Bauhaus, those of Japanese master Masahiro Chatani [Chatani 1984] and British paper artist Paul Jackson [Jackson 2014].Cuts, folds, linear divisions, and symmetrical repetitions make it possible to move from the two-dimensionality proper of paper to the three-dimensionality of the model. The research and related practice presented here converged in the Paper City Tales workshop at the Politecnico di Torino, held in the MODLab Arch model laboratory, developed by the authors, and coordinated by Prof. Marco Vitali. This experience saw third- and fourth-year students from Piedmont high schools try to construct Calvinian Invisible Cities.
Keywords: invisible cities; Italo Calvino; model; paper; imaginary cities